Empreendedorismo e open innovation: uma análise de projetos de base tecnológica - Desidério, Paulo Henrique Martins (2012)
The context of a new corporate behavior of interaction can provide the formation of numerous prospects for action in the markets. Innovative ideas, entrepreneurs and culture prone to take risks are intangible factors to the development of a region. Combined with the tangible aspect, the initial capital, produce business ideas transformers. For the consolidation of a dynamic local productive sector, it is important that businesses invest in cutting-edge research and have qualified professionals. In addition to the sharing of costs in research and development, the open innovation diversifies the interactives agents of a particular innovation. At the beginning of the 21st century, the availability of information in the internet environment and the exponential growth of network operations on shared experiences provide access to business models at a pace unimagined by corporations. The note if closed models of innovation management, known as closed innovation, don´t be longer sufficient to monitor the dynamics of the market, forcing adaptations to new contexts and searches more amplified of innovations and partnerships that leverage existing business models, which may be worn by the market and stimulating a strategic direction for the new most competitive and effective settings. For small businesses, innovations can be generated by partnering with established companies to share production structures and provides an additional growth than be opting by an isolate actuation (BARON; SHANE, 2007). This provides synergy in acquisition of components with suppliers, in obtaining financing, at access to existing assets such as manufacturing plants, sales, and knowledge in product development and brand itself. There is also the possibility to participate in incubator programs, as generally developed on college campuses. This possibility allows companies to contact with new technology research, while it is assisted in managing your business innovator, contributing with expertise to transform marketing concepts into market possibilities. The objective of this research is the presentation of some projects in the technology-based identified at Fiat Automóveis as strategic direction to open innovation (CHESBROUGH, 2003, 2006; CHRISTENSEN, 2006; MEER, 2007). The methodological context is a qualitative approach and descriptive at entrepreneurship theme and exploratory in open innovation concept, with actions of research in open innovation literature, entrepreneurship and entrepreneurial practices, plus archival research and semistructured interviews in the case study. Is shown the role of society, customers, universities, development entities and incubators in the technological innovation projects with the strategy of capturing ideas and concepts through open innovation. Was presented the way of technology-based projects in the organization and their interactions with external stakeholders relevant to your formatting. The survey results show the potential that collaborative partnerships and knowledge can to provide competitiveness and success of the actors involved with the adoption of an effective process for managing internal and external innovation.